TECHNOLOGY USE IN TEACHING LITERATURE AMID AND POST-PANDEMIC: TEACHERS’ PERCEPTIONS - Erina Andriani; Barli Bram (Universitas Muhammadiyah Metro, 2022)
The impact of the COVID-19 pandemic caused the teaching-learning process to be done online. The online learning environment required EFL teachers to increase their technology use, including teaching literature classes. This influenced the teachers’ technology use in the long run, especially in post-pandemic teaching. To the best of researchers’ knowledge, only a few studied teachers’ perceptions of their technology use in EFL teaching and the post-pandemic era, especially for teaching literature. Therefore, this study aimed to investigate EFL teachers’ perceptions of their technology use for teaching literature and the technology use for teaching literature in the post-pandemic era. This study used a narrative inquiry design and a semi-structured interview to gather data from six senior high school teachers and analyzed using thematic analysis. The results showed that teachers had challenges in using technology for teaching literature at first because of low experience, but they had positive views on their current technology use for teaching literature, had positive perceptions on hybrid learning, and perceived that they had to make more adjustments for teaching literature in the post-pandemic era. This study may help teachers reflect on their technology use and adjust their technology use in online learning to meet the needs of the teachers and students.